An Overview of the Studies of Health Information Systems in Turkey - Sebetci, O; Aksel, M (International Journal of Computer Sciences and Engineering, 2025)
This paper presented a literature review about health information systems. Health information technology gives information about health section data and data generation, compilation, analyses and gives reliable information for policy and system development. Health information technology is based on efficiency, quality and cost of healthcare. There are positive influences of health information technologies on healthcare, but also some difficulties and failures that need more detail investigations in the future. The aim of this paper is given literature information for overview of health information systems in Turkey and other countries' systems. The results would provide a useful approach for evaluating the positive and negative factors and give ideas for the health information system users and researcher in Turkey.